Comparative Legal Research on Contract Law Changes Under Covid-19 Pandemic: England, United States, Asia and Ukraine - Писаренко, Марина Олександрівна; Писаренко, М. О.; Писаренко, Марина Александровна; Pysarenko, Maryna O.; Граніна, Іванна Віталіївна; Граніна, І. В.; Гранина, Иванна Витальевна; Hranina, Ivanna V.; Воротинцева, Інна Валеріївна; Воротинцева, І. В.; Воротынцева, Инна Валерьевна; Vorotyntseva, Inna V. (Los Hemisferios University, 2021)
The study aims to characterize the changes in contract law under the influence of the Covid-19 pandemic in Ukraine and the world. For this purpose, we used systemic, comparative-legal, and formal-legal methods. The paper consists of an introduction, methodology section, bibliography review, results, discussion, conclusions, and references. In the result of the study some distinctive features of changes in contract law under Covid-19 pandemic at the level of national law of Ukraine and some foreign countries were characterized and highlighted. The authors came to the conclusion that changes in contract law are typical for the countries of continental law. Instead, common law states remain resistant to changes in contract law, particularly, the force-majeure application. The reason for this lies in the specific doctrine of the common law countries, as England and the United States. These countries’ courts remain unshakable in terms of managing the contracts performance. In contrast, some Asian and European states (including Ukraine) are characterized by dynamic changes in legislation, given the pandemic situation. The paper also discusses similar institutions like hardship and frustration of purpose, which are both applicable in continental and common law countries.

Дослідження має на меті охарактеризувати зміни договірного права під впливом пандемії Covid-19 в Україні та світі. Для цього використовували системний, порівняльно-правовий та формально-правовий методи. Стаття складається із вступу, розділу методології, огляду літератури, результатів, обговорення, висновків та посилань. У результаті дослідження охарактеризовано та виділено деякі особливості змін договірного права в умовах пандемії Covid-19 на рівні національного законодавства України та деяких зарубіжних країн. Автори дійшли висновку, що зміни договірного права характерні для країн континентального права. Натомість держави загального права залишаються стійкими до змін договірного права, зокрема, до застосування форс-мажорних обставин. Причина цього полягає в специфічній доктрині таких країн загального права, як Англія та США. Суди цих країн залишаються непохитними з точки зору управління виконанням контрактів. Навпаки, деякі азіатські та європейські держави (включаючи Україну) характеризуються динамічними змінами законодавства, враховуючи ситуацію з пандемією. У статті також обговорюються подібні інститути, такі як суттєва зміна обставин (hardship) та недосяжність мети договору (frustration of purpose), які застосовні як у країнах континентального, так і загального права.
Vorotyntseva I. Comparative legal research on contract law changes under COVID-19 pandemic: England, United States, Asia and Ukraine / I. Vorotyntseva, I. Hranina, M. Pysarenko // IUS HUMANI-REVISTA DE DERECHO. - Los Hemisferios University, 2021. - Vol. 10. - Issue 1. - Р. 123-150.
Keywords: Contract Law; Force Majeure; Contract Performance; Hardship; Frustration of Purpose; договірне право; форс-мажор; виконання контракту; суттєва зміна обставин; недосяжність мети договору; Research Subject Categories::LAW/JURISPRUDENCE